Invertebrate research overview: 2. The endemic land snails - Coppois, Guy (Bulletin de l'Institut Royal des Sciences Naturelles de Belgique, 2000)
Keywords: naesiotus count

Biological peculiarities of oceanic islands - Gulick, Addison (The Quarterly Review of Biology, 1932)
Keywords: naesiotus count

Land snails of the Galápagos - Smith, Allyn G. (The Galápagos; Proceedings of the Symposia of the Galápagos International Scientific Project, 1966)
Keywords: naesiotus count

Mitochondrial genome sequence of the Galápagos endemic land snail \textit{Naesiotus nux - Hunter, Samuel S.; Settles, Matthew L.; New, Daniel D.; Parent, Christine E.; Gerritsen, Alida T. (Genome Announcements, 2016)
We report herein the draft mitochondrial genome sequence of Naesiotus nux, a Galápagos endemic land snail species of the genus Naesiotus. The circular genome is 15 kb and encodes 13 protein-coding genes, 2 rRNA genes, and 21 tRNA genes.
Keywords: naesiotus count

Galápagos bulimulids: status report on a devastated fauna - Parent, C.E.; Smith, R.P. (Tentacle, 2006)
Keywords: naesiotus count

l'Interet des mollusques aux iles Galapagos - Van Mol, Jean-Jacques (Noticias de Galápagos, 1971)
Keywords: naesiotus count

Biogeography of Galápagos land snails - Chambers, Steven M. (Galápagos marine invertebrates: taxonomy, biogeography, and evolution in Darwin's islands, 1991)
Keywords: Galapagos Islands; Marine invertebrates; naesiotus count

CDF checklist of Galápagos terrestrial and brackish water snails—FCD Lista de especies de caracoles terrestres de Galápagos. - Parent, Christine E.; Miquel, Sergio E.; Coppois, Guy (Charles Darwin Foundation/Fundación Charles, Darwin, Galápagos., 2014)
Keywords: naesiotus count

Threatened galapagos bulimulid land snails: an update - Coppois, Guy (The conservation biology of molluscs : proceedings of a symposium held at the 9th International Malacological Congress, Edinburgh, Scotland, 1986 including a status report on molluscan diversity, 1995)
Keywords: naesiotus count

Threatened Galápagos snails - Coppois, Guy; Wells, Sue (Oryx, 1987)
Keywords: naesiotus count

Sequential colonization and diversification of Galápagos endemic land snail genus \textit{Bulimulus (Gastropoda, Stylommatophora) - Parent, Christine E.; Crespi, Bernard J. (Evolution, 2006)
Species richness on island or islandlike systems is a function of colonization, within-island speciation, and extinction. Here we evaluate the relative importance of the first two of these processes as a function of the biogeographical and ecological attributes of islands using the Galápagos endemic land snails of the genus Bulimulus, the most species-rich radiation of these islands. Species in this clade have colonized almost all major islands and are found in five of the six described vegetation zones. We use molecular phylogenetics (based on COI and ITS1 sequence data) to infer the diversification patterns of extant species of Bulimulus, and multiple regression to investigate the causes of variation among islands in species richness. Maximum-likelihood, Bayesian, and maximum-parsimony analyses yield well-resolved trees with similar topologies. The phylogeny obtained supports the progression rule hypothesis, with species found on older emerged islands connecting at deeper nodes. For all but two island species assemblages we find support for only one or two colonization events, indicating that within-island speciation has an important role in the formation of species on these islands. Even though speciation through colonization is not common, island insularity (distance to nearest major island) is a significant predictor of species richness resulting from interisland colonization alone. However, island insularity has no effect on the overall bulimulid species richness per island. Habitat diversity (measured as plant species diversity), island elevation, and island area, all of which are indirect measures of niche space, are strong predictors of overall bulimulid land snail species richness. Island age is also an important independent predictor of overall species richness, with older islands harboring more species than younger islands. Taken together, our results demonstrate that the diversification of Galápagos bulimulid land snails has been driven by a combination of geographic factors (island age, size, and location), which affect colonization patterns, and ecological factors, such as plant species diversity, that foster within-island speciation.
Keywords: Adaptive radiation; colonization; Galápagos; land snails; naesiotus count; speciation; species richness

Trade-offs direct the evolution of coloration in Galápagos land snails - Kraemer, A. C.; Philip, C. W.; Rankin, A. M.; Parent, C. E. (Proceedings of the Royal Society B: Biological Sciences, 2019)
Keywords: naesiotus; naesiotus count

Assessment of snail exposure to the anticoagulant rodenticide brodifacoum in the Galapagos Islands - Parent, C. E.; Fisher, P.; Jolley, W.; Alifano, A.; Campbell, K.J. (Island invasives: scaling up to meet the challenge. Proceedings of the international conference on island invasives 2017, 2019)
00000
Keywords: naesiotus; naesiotus count

Evolution and speciation among a vanishing tribe - Parent, C. E.; Coppois, G (Galápagos: preserving Darwin's legacy, 2009)
00000 OCLC: 636258077
Keywords: naesiotus count

Snails going extinct at speed - Wells, Susan (New Scientist, 1988)
00000
Keywords: naesiotus count

Determinants of species richness and trait diversity in galapagos’ native biota - Roell, Yannik (University of Idaho, 2017)
00000
Keywords: naesiotus; naesiotus count; naesiotus maps

Reviving Galápagos snails: ancient DNA extraction and amplification from shells of probably extinct endemic land snails - Villanea, Fernando A.; Parent, Christine E.; Kemp, Brian M. (Journal of Molluscan Studies, 2016)
Keywords: naesiotus count

History of invertebrate zoology at the California Academy of Sciences - Williams, Gary C. (Proceedings of the California Academy of Sciences, Fourth Series, 2007)
Keywords: naesiotus count

Two different striation patterns of the protoconch in Galapagos Bulimulidae: an SEM study - Coppois, G.; De Vos, Louis (Journal of Molluscan Studies, 1986)
Keywords: naesiotus count

Distribution of bulimulid snails along the northern slope of Santa Cruz Island, Galapagos - Coppois, Guy (Biological Journal of the Linnean Society, 1984)
Keywords: naesiotus count; naesiotus maps